Dynamics of suspended sediment in the Južna Morava river, south-eastern Serbia - Manojlović Sanja; Dobrić Milica; Petronijević Jovan (Glasnik Srpskog Geografskog Društva)
This study estimate the temporal trends of recent suspended sediment in Južna Morava river. The variations of suspended sediment transport were analyzed at different time scales (inter-annual, monthly and seasonal, among different periods), based on 47-year hydrological data from the outlet hydrological station. The results indicate of a decline in suspended sediment concentration and sediment load in the long-time series, which can be divided into three periods: high SSC or Qs (1961-1976), medium SSC or Qs (1977-1988) and low SSC or Qs (1989-2007). The average annual SSC and Qs of these three periods are SSC=0.7284 g/l, SSC=0.3580 g/l, SSC=0.1865 g/l, and Qs=4260x103 t, Qs=2277 x103 t, Qs=789 x103 t, respectively. The decrease in SSC and Qs is at the significance level of α=0.001. The frequency distribution of the daily SSC show that cumulatively 92% of daily SSC during the low stage was u distributed in classes up to 0.5 g/l, versus 82% during the medium and 67% during the high period. The frequency of daily SSC in the class of 1-5 g/l decreases over time, from 14% in high period to 6% in low period. In the period 1989-2007 have not been reported SSC greater than 5 g/l. Different patterns of suspended sediment concentration SSC-Q hysteretic loops have been observed for each period. Two types of hysteretic loops were found at Južna Morava River: figure-eight typical of periods 1961-1976 and 1978-1988 and counter-clockwise in period 1989-2007. Human impact is the main factor in reducing suspended sediments. An important change in agriculture land in the basin recorded a significant impact on sediment transport.